Antioxidant and Anti-Inflammatory Effects of Origanum majorana L. Methanolic Extract on Bile Duct Ligation in Male Rats. (7th May 2021) - Gheitasi, Izadpanah; Motaghi, Nikta; Sadeghi, Hossein; Sadeghi, Heibatollah; Moslemi, Zahra; Eftekhari, Mahdieh; Shakerinasab, Nasrin; Doustimotlagh, Amir Hossein
Abstract : Introduction . Cholestasis is caused by malfunction of the hepatobiliary system. This disorder is the result of the accumulation of bile fatty acids and other toxins in the liver. The aim of the current study was to investigate the antioxidative and hepatoprotective effects of methanolic extract of Origanum majorana L. (OM) on hepatic disorder and tissue damage induced by bile duct ligation (BDL) in rats. Materials and methods . Twenty-eight male Wistar rats were randomly divided into 4 groups including sham control group received vehicle (SC-V), bile duct ligation received vehicle (BDL-V), bile duct ligation group received OM extract (BDL + OM), and sham control group received OM extract (SC + OM). One day after surgery, the animals received vehicle or methanolic extract of OM 300 mg/kg/day for 7 consecutive days by oral gavage. Finally, the animals were anesthetized and the blood samples were collected from each animal. After sacrificing of animals, liver tissue from each rat was removed and divided into three parts: one part was used for preparing of homogenized tissue, one part was fixed in 10% neutral formalin for histopathology examination, and the third part was kept in liquid nitrogen for gene expression analysis. Biomarkers of oxidative stress in the liver tissue and serum, as well as histopathological changes of the liver, were assessed. Also, the gene expression of IL-1, TNF- α, TGF- β, and α -SMA has been measured. Results . The results showed that BDL-V significantly increased the activity of ALT, AST, ALP, and total bilirubin compared to the SC-V group. The oxidative stress markers such as MDA and FRAP significantly increased due to BDL, while the CAT activity reduced in the BDL-V group compared to SC-V group. Oral treatment with OM reduced ALT and AST activity, although it was not statistically significant. OM treatment considerably increased the activity of CAT compared to BDL group. BDL-V induced a significant histological change in the liver, while treatment with OM at a dose of 300 mg/kg showed a minor effect on histopathological changes. In addition, the mRNA of IL-1, TNF- α, TGF- β, and α -SMA significantly increased in the BDL-V group, while treatment with OM only significantly reduced TGF- β in comparison with BDL-V rats. Conclusions . The results of the present study showed that oral administration of OM extract had a moderate protective effect on cholestasis due to BDL. Indeed, more studies with different doses of extract are needed to confirm this finding.